Scaffolds for 3D Cell Culture and Cellular Agriculture Applications Derived From Non-animal Sources - Campuzano, Santiago; Pelling, Andrew E. (Frontiers in Sustainable Food Systems, 2019)
For decades, two-dimensional cell culture has been regarded as a major tool in cellular and molecular biology due to its simplicity, reproducibility and reliable nature. However, it is now recognized that 2D cell culture underrepresents the in vivo environment of living cells. The development and use of 3D scaffolds and biomaterials provide researchers an ability to more closely mimic the in vivo environment. However, many biomaterials are of animal origin, leading to variability, environmental and ethical concerns. Here we present three animal-free scaffolds: decellularized plant tissue, chitin/chitosan and recombinant collagen. Decellularized plant tissue provides a wide array of structures with varying biochemical, topographical and mechanical properties; chitin/chitosan-based scaffolds have shown synergistic bactericidal effects and improved cell-matrix interaction; and lastly, recombinant collagen has the potential to closely resemble native tissue, as opposed to the other two. These benefits, alongside potential scalability and tunability, open the door to applications beyond the biomedical realm, such as innovations in cellular agriculture and future food technologies.